2018
DOI: 10.1159/000489345
|View full text |Cite
|
Sign up to set email alerts
|

Sequential Dexamethasone and Aflibercept Treatment in Patients with Diabetic Macular Edema: Structural and Functional Outcomes at 52 Weeks

Abstract: Objective: The aim of this paper is to compare intravitreous aflibercept versus dexamethasone implant followed by aflibercept (sequential treatment group) in patients with diabetic macular edema (DME). Methods: We conducted an observational retrospective study in naïve DME patients, 15 treated only with aflibercept (a monthly injection for the first 5 consecutive doses, followed by an injection every 2 months), and 15 treated with a single dexamethasone implant followed by bimonthly aflibercept. Best-corrected… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
10
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(11 citation statements)
references
References 16 publications
1
10
0
Order By: Relevance
“…9 In contrast, the results from trials with less strict PRN treatment criteria show diminished BCVA gains and fewer injections in year 1 compared with trials with more rigorous regimens. 6,9,24,25 When looking for baseline characteristics that may influence the outcome, we noted that the 12-month change in BCVA negatively correlated with baseline BCVA in patients with DME, which is consistent with prior studies noting a negative correlation between baseline BCVA and long-term BCVA change. 91,92 This has been described as a "ceiling effect" in which the visual acuity gained by anti-VEGF and dexamethasone implant use reaches a maximum over the time-course of treatment.…”
Section: Discussionsupporting
confidence: 88%
“…9 In contrast, the results from trials with less strict PRN treatment criteria show diminished BCVA gains and fewer injections in year 1 compared with trials with more rigorous regimens. 6,9,24,25 When looking for baseline characteristics that may influence the outcome, we noted that the 12-month change in BCVA negatively correlated with baseline BCVA in patients with DME, which is consistent with prior studies noting a negative correlation between baseline BCVA and long-term BCVA change. 91,92 This has been described as a "ceiling effect" in which the visual acuity gained by anti-VEGF and dexamethasone implant use reaches a maximum over the time-course of treatment.…”
Section: Discussionsupporting
confidence: 88%
“…Twenty-four studies commented on safety outcomes, including 14 studies reporting ocular adverse events 5 17 18 19 23 24 25 26 27 28 29 30 31 32 and 10 reporting no ocular adverse events with aflibercept. 15 16 20 21 22 33 34 35 36 37 The most commonly reported ocular adverse event was subconjunctival hemorrhage (164 cases of 2516 aflibercept-treated eyes with ocular safety data available, representing a prevalence of 6.5%). 24 26 27 30 31 32 Twelve studies reported APTC-defined adverse events with aflibercept treatment.…”
Section: R Esultsmentioning
confidence: 99%
“…At start of treatment, intensive anti-VEGF treatment and DEX implant led to better functional and anatomical outcomes than less intense treatment. In another study, Hernández-Bel et al [ 24 ] reported that sequential intravitreal treatment in DMO starting with dexamethasone and followed by aflibercept was a reasonable alternative to treatment with aflibercept alone for reducing the burden of treatment over 12 months. A difference noted in comparison with our study was that the improvement in vision and the decrease in macular thickness were not statistically significant.…”
Section: Discussionmentioning
confidence: 99%